Effects of Quaternary-Ammonium-Based Formulations on Bacterial Community Dynamics and Antimicrobial Susceptibility - McBain, Andrew J. (American Society for Microbiology, 2004)
Quaternary ammonium compounds (QACs) are widely used as adjuncts to hygiene in domestic cleaning products. Current concern that the increased use of such biocides in consumer products might contribute to the emergence of antibiotic resistance has led us to examine the effects of a QAC-containing domestic cleaning fluid on the population dynamics and antimicrobial susceptibility of domestic sink drain biofilm communities. QAC susceptibilities of numerically dominant, culturable drain bacteria (15 genera, 17 species) were determined in vitro before and after repeated QAC exposure (14 passages). A fully characterized drain microcosm was then exposed to short-term (12 days) and long-term (3 months) dosing with a QAC-containing domestic detergent (QD). QAC exposure of isolated cultures caused both increases (three species) and circa twofold decreases (six species) in QAC susceptibility. The susceptibility of Ralstonia sp. was considerably decreased following 14 consecutive QAC passages. Control drain microcosm biofilms maintained dynamic stability, as evidenced by culture and denaturing gradient gel electrophoresis (DGGE) analysis. Bacterial population densities were largely unaffected during short-term exposure to use levels of QD, although 50% QD caused circa 10-fold viability reductions. DGGE analysis supported these observations; identified the major microcosm genera as Pseudomonas, Pseudoalteromonas, Erwinia, and Enterobacter, and showed that aeromonads increased in abundance under 10 to 50% QD. Long-term exposure of the microcosms to QD did not significantly alter the pattern of antimicrobial susceptibility. These data demonstrate the recalcitrance of domestic drain biofilms toward QAC and that although repeated QAC exposure of drain isolates in pure culture results in susceptibility change in some test bacteria, such changes do not necessarily occur within complex communities.